2020
DOI: 10.1007/s12640-020-00227-8
|View full text |Cite
|
Sign up to set email alerts
|

Four Synthetic Cathinones: 3-Chloromethcathinone, 4-Chloromethcathinone, 4-Fluoro-α-Pyrrolidinopentiophenone, and 4-Methoxy-α-Pyrrolidinopentiophenone Produce Changes in the Spontaneous Locomotor Activity and Motor Performance in Mice with Varied Profiles

Abstract: Two chloromethcathinones, 3-chloromethcathinone (3-CMC) and 4-chloromethcathinone (4-CMC), and two para-substituted α-pyrrolidinophenones, 4-methoxy-α-pyrrolidinopentiophenone (4-MeO-PVP) and 4-fluoro-α-pyrrolidinopentiophenone (4-F-PVP), represent synthetic cathinones, the second most frequently abused group of new psychoactive substances (NPSs), which has aroused a worldwide health concern in the last decade. Synthetic cathinones act as psychostimulants by elevating extracellular levels of monoaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Drug-induced dopaminergic activity parallels the locomotor stimulation and rewarding effect [ 118 , 143 , 144 ]. Methylone is a nonspecific substrate [ 118 ], producing an inward current at SERT but not at DAT, similarly to MDMA [ 145 ], and oxidative stress, which is responsible for the neurotoxicity of methylone and, to a greater extent, MDPV [ 146 ]. 4-MEC, 4-MePP, and α-PVP also mainly block DAT, with greater abuse potential compared to other stimulants [ 147 , 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drug-induced dopaminergic activity parallels the locomotor stimulation and rewarding effect [ 118 , 143 , 144 ]. Methylone is a nonspecific substrate [ 118 ], producing an inward current at SERT but not at DAT, similarly to MDMA [ 145 ], and oxidative stress, which is responsible for the neurotoxicity of methylone and, to a greater extent, MDPV [ 146 ]. 4-MEC, 4-MePP, and α-PVP also mainly block DAT, with greater abuse potential compared to other stimulants [ 147 , 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…Selection of a mouse strain was based on published data indicating low basal immobility of DBA/2J mice in forced swim and tail suspension tests, allowing for more sensitive detection of potential depressive effects, and its sensitivity to acute desipramine and fluoxetine as well as chronic lithium treatment (Can et al 2011;Lucki et al 2001). Moreover, the behavioral characteristics of DBA/2J mice differ markedly from previously used C57BL/6J (Võikar et al 2005;Wojcieszak et al 2020). Therefore, it was used to confirm whether previous findings regarding the effects of 4-CMC and 4-MeO-PVP are independent of genetic background.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…The acute effects of 4-CMC and 4-MeO-PVP on the spontaneous activity of mice were first assessed to select the drug doses to be used in later studies requiring multiple treatments. Spontaneous locomotor activity was measured according to Wojcieszak et al ( 2020 ) with minor modifications, using Opto-Varimex Auto-Track (model 0271-002M, Columbus Instruments, Columbus, OH, USA) open field chambers (20.3 × 20.3 × 20.3 cm; 4 units) equipped with 16 infrared beams and corresponding photodetectors, spaced by 1.3 cm; these were located on the X and Y horizontal axes, on two planes, to detect both horizontal and vertical movements.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported by [31,32] have demonstrated that para-halogenated αpyrrolidinophenones act as potent DA uptake inhibitors. Regarding the in vivo effects, the authors of [33] recently demonstrated that 4-F-α-PVP administration induces a dosedependent increase in horizontal locomotor activity in mice. Additionally, 3-F-α-PVP and 3-Br-α-PVP are also available through the internet, and some samples have been identified in non-governmental organizations' (NGOs') drug testing laboratories (i.e., www.drugsdata.org; www.ecstasydata.org, accessed on 20 December 2021); although, to our knowledge, there is no information regarding the pharmacology of these metahalogenated derivatives.…”
Section: Introductionmentioning
confidence: 99%